The Olongapo-Subic Bay urban link revitalizing the city-freeport connection - Guanzon, Allen John T.; Luna, Market Cesar A. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
This Comprehensive Design Project explores the urban cultural landscape of Olongapo City and Subic Bay Freeport Zone, a former American Naval Base turned freeport, as a product of their unique and shared historical context, starting from the Spanish Navy Era up to the present. Through the analysis pf the sites' people, places, and traditions, issues of identity, movement and development arose - issues which revolve around the remnants of the past, needs of the present and direction towards the future. With these in mind, the project aims to forward the creation of an integrated city-freeport development in the future which addresses the needs of the present population, while highlighting the stories relationship of the sites in the past. This led to two interventions: first is the creation of a conceptual city-freeport revitalization plan on the macrolevel which rethinks the redevelopment and linkage of the city and the freeport's central business districts; second is the design of the Olongapo- Subic Bay Urban Link on the microlevel. The design is a reimagining of the Magsaysay Bridge as an urban park and the Freeport Main Gate lot as a mixed-use urban facility which would act as a both a transition and a linkage between the city and the freeport. Through following the principles of urban catalyst approach and designing for historic urban quarters, the over-all design aims to reimagine a shared future for the city and freeport by bridging the present to their storied past.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Free ports and zones -- Philippines -- Subic Bay